Genetic structure and local adaptation of Nitraria sphaerocarpa populations from arid northwestern China - Ma, Wenhui; Zhang, Jian; Tian, Haowen; Li, Yan; Zhang, Hongxiang (Frontiers in Plant Science, 2025)
IntroductionUnderstanding the genetic basis of local adaptation in non-model species is one of the fundamental goals in ecological and evolutionary biology. Researches on the genetic mechanisms of local adaptation in desert plants is crucial to comprehend how species adapt to heterogeneous environments in arid regions under the background of climate warming.MethodsIn this study, the typical superxerophytic constructive species of Nitraria sphaerocarpa, which is fragmentarily distributed in arid northwestern China, was sampled with 20 populations. A total of 10,828 high-quality SNPs were obtained by ddRAD-seq from 200 individuals of N. sphaerocarpa populations across the northwestern China, based on which the population genetic and local adaptation of N. sphaerocarpa was investigated.ResultsThe results showed that the population genetic diversity of N. sphaerocarpa was low. Twenty populations could be clustered into four lineages, which began to diverge in the Pleistocene. Mantel test showed that population differentiation was caused by geographical and environmental factors. Through gradient forest (GF), redundancy analysis (RDA) and niche comparison analyses, it was found that both temperature and precipitation factors affected the genetic differentiation of N. sphaerocarpa populations. Twenty-two loci associated with local adaptation were identified by environmental association analysis (EAA) using LFMM and RDA. Three successfully annotated environmental adaptive loci (EAL) were related to physiological processes in response to abiotic stresses such as drought, heat and cold.DiscussionIn conclusion, the spatial genetic structure of N. sphaerocarpa populations showed a fragmented pattern in the latitude gradient. The main pressure of environmental adaptation was the changes of temperature and precipitation. Physiological adaptation appears to be an important mechanism in response to environmental stress.